К изучению фауны совок Крыма. Сообщение IV. Подсемейство Cuculliinae (Noctuidae, Lepidoptera) - Ключко, 3.Ф. (Вестник зоологии, 1969)
As a result of analysing the three-year collections of the entomological expeditions from Kiev University and literary data 68 species of Cuculliinae subfamily were registered in the Crimean Noctuidae fauna, 38 species of them being stated in the Crimea for the first time. The following five species—Episema grueneri B., Dasypolia templi Thnbg.. Agrochola humilis Schiff., Lithophane lapidea H b., Spudaea ruticilla E s p.— are proved •to be new for the Ukrainian fauna and the Crimean subspecies of the latter (it is described -as ssp, por.tica К I j u t s h к o) is new for science.
For Cuculliinae development the natural conditions of the South Crimea coast are the most favourable. Almost all of the species of the subfamily occur there. Typically steppe species of the genera Episema O., Ulochlaena Led are spread in the steppe and north foothills. At the South Crimea coast they are met only in the environs of Sevastopol. In the Crimea the Cuculliinae of the pont-Mediterranean and Eurasian groups are predominant.